The Disappearance Behavior, Residue Distribution, and Risk Assessment of Kresoxim-Methyl in Banana (Musa nana Lour.) Based on a Modified QuEChERS Procedure Using HPLC-MS/MS - Wang, Siwei; Sun, Haibin; Liu, Yanping; Wang, Xiaonan; Chang, Hong (Frontiers in Environmental Science, 2022)
A modified-QuEChERS method for determination of kresoxim-methyl in banana and soil was developed and validated via high performance liquid chromatography-tandem mass spectrometry technique (HPLC-MS/MS). The dissipation behavior, residue distribution and risk assessment of kresoxim-methyl in banana were further investigated based on this method. The dissipation behavior of kresoxim-methyl in banana and soil were described by using first-order kinetics and its half-life, as they were 4.8-5.7 d and 5.5-6.5 d, respectively. The concentrations of kresoxim-methyl were 0.03–0.08 mg kg-1, 0.06–0.17 mg kg-1, and <0.01 mg kg-1 in whole banana, peel and pulp, respectively, on the basis of spraying three times and pre-harvest interval (PHI, 42 days) at recommended dosage. The results showed that the risk quotient (RQ) of kresoxim-methyl in banana to people exhibited an acceptably low dietary risk. This current study could help in guiding the scientific and proper usage of this formulation.